2000
DOI: 10.3109/07357900009012192
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating B-Cell-Derived IgG Recognizes Tumor Components in Human Lung Cancer

Abstract: Tumor-infiltrating lymphocytes consist predominantly of T cells, whereas B cells, plasma cells, and natural killer cells are observed with different degrees of frequency. We investigated the nature of tumor-infiltrating B lymphocytes (TIB) in human lung cancer. First, to examine the ability of immunogloblin production by TIB, cancer tissues were subcutaneously transplanted in severe combined immunodeficient mice, and the murine serum was examined for the concentration of human immunogloblin. Human IgG (huIgG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…(28)(29)(30)(31) We focused our attention on the role of TIB in the tumor-specific immune response. In a previous study, (24) we showed that TIB produce IgG in SCID mice when lung cancer tissue is xenotransplanted. Furthermore, we applied the TIB-derived IgG to the SEREX method and identified 37 antigens in a patient with lung cancer (A904).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(28)(29)(30)(31) We focused our attention on the role of TIB in the tumor-specific immune response. In a previous study, (24) we showed that TIB produce IgG in SCID mice when lung cancer tissue is xenotransplanted. Furthermore, we applied the TIB-derived IgG to the SEREX method and identified 37 antigens in a patient with lung cancer (A904).…”
Section: Discussionmentioning
confidence: 99%
“…We found that human IgG was produced by TIB in the serum of SCID mice, and western blot analysis revealed that such human IgG could react with the proteins from tumor lysates. ( 24 ) Williams et al. also reported that the serum from tumor‐engrafted SCID mice could react with the high and low molecular weight proteins derived from both the membrane and cytosolic fractions of tumor cell lysates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical implantation of non-disrupted human lung tumor tissue ( Figure 1) revealed the following: (1) Successful engraftment of hu-TIL occurs in more than 95% of patient tumors xenografted, regardless of the histological type of tumor (63); (2) Human TIL remain at the site of the xenograft and show evidence of proliferation in situ (63); (3) The huIg present in the SCID mouse sera is primarily IgG (167) and is produced by human plasma cells in T-cell dependent manner (63); (4) Sera from xenografted mice contain antibodies that react against proteins derived from autologous tumor tissue (63,167), as well as allogeneic lung tumor cell-lines (167), but not normal lung tissue (167); (5) High levels of huIg in the sera of mice engrafted with tumor biopsy tissue are associated with the growth arrest of adenocarcinoma xenografts (63); and (6) Serial passage of lung tumor Data obtained from gene array analysis of human lung tumor xenografts following treatment in vivo. Xenografts were established s.c. in SCID mice from a patient lung tumor biopsy specimen, and treated one week later by direct intra-tumoral injection of biodegradable microspheres loaded with recombinant human IL-12, or control (cytokine-free) BSA-loaded microspheres.…”
Section: Natural Human Tumor Microenvironments Established By Engraftmentioning
confidence: 99%
“…Previous studies demonstrated that TIB produce IgG in SCID mice xenotransplanted with human lung cancer tissue. (10)(11)(12)(13)20) TIB-derived IgG was analyzed by the SEREX method and 22 antigens were identified in a patient with lung cancer. A mutated p53 was one of the identified antigens and the change in the antibody titer against mutated p53 was correlated with the clinical course of the patient.…”
Section: Discussionmentioning
confidence: 99%